2021
DOI: 10.1136/jitc-2020-001649
|View full text |Cite
|
Sign up to set email alerts
|

TGM4: an immunogenic prostate-restricted antigen

Abstract: BackgroundProstate cancer is the second leading cause of cancer-related death in men in the USA; death occurs when patients progress to metastatic castration-resistant prostate cancer (CRPC). Although immunotherapy with the Food and Drug Administration‐approved vaccine sipuleucel‐T, which targets prostatic acid phosphatase (PAP), extends survival for 2–4 months, the identification of new immunogenic tumor-associated antigens (TAAs) continues to be an unmet need.MethodsWe evaluated the differential expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 67 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…It has previously been demonstrated that human TGM4 is expressed in several tissues but with a minimum of 200 times lower level than in the prostate [30]. Recently, other studies got a similar conclusion at both RNA and protein levels that human TGM4 expression exists, but it is minimal in nonprostatic tissues [31]. In mice, TG4 is also expressed at the protein level in the vena cava and aortic smooth muscle cells [8].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has previously been demonstrated that human TGM4 is expressed in several tissues but with a minimum of 200 times lower level than in the prostate [30]. Recently, other studies got a similar conclusion at both RNA and protein levels that human TGM4 expression exists, but it is minimal in nonprostatic tissues [31]. In mice, TG4 is also expressed at the protein level in the vena cava and aortic smooth muscle cells [8].…”
Section: Discussionmentioning
confidence: 86%
“…The missing cellular negative GTP regulation of hTG4 can support its effect on tumour invasiveness. In prostate cancer cells, the presence of hTG4 is a negative prognostic marker [31]. Further studies with hTG4 inhibitors would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…As 80%, on average, of the targets were expressed in any EV sample (Table S13), we restricted our analysis to mRNAs expressed in at least a 5-fold higher level in the primary patient EV samples than in the post-RP sample of P33, thereby attempting to focus on detectable transcripts from prostate, PCa or metastasis. As positive controls for this strategy, we checked the expression of SPDEF, a known uEV biomarker with roles in PCa initiation and progression [47] and TGM4, detected in uEV with enriched expression in prostate and PCa tissues and correlated with unfavourable prognosis [19,48]. The expression of SPDEF and TGM4 mRNA were >5-fold higher in all three primary PCa patient uEV samples, relative to the post-RP uEV sample (Table S4).…”
Section: Mirna Namementioning
confidence: 99%
“…More recent discoveries uncovered the heterogeneity of metabolic reprogramming in cancer cells to also include increases in oxidative phosphorylation and the use of alternative carbon sources (i.e., glutamine, fatty acids, and serine). Various studies have revealed a metabolic regulation system between cancer cells, immune cells, and stroma and have demonstrated the targetability of these metabolic shifts in preventing disease progression (151)(152)(153)(154)(155)(156)(157)(158). Surprisingly, studies have also revealed regulation and correlation between metabolic shifts and cytoskeletal proteins in cancer.…”
Section: Targeting Cytoskeletal and Metabolic Connectionsmentioning
confidence: 99%